Mechanical testing of micromolded plastic parts by nanoindentation - Zhiltsova, Tatiana (2018)
Weld lines occur when two melt streams are combined. They may result in purely cosmetic imperfections, but also may represent part failure if placed in an area on the plastic highly subjected to stress during service. Qualitative assessment of these structural and cosmetics defects is usually accomplished by conventional mechanical characterization, destructive by nature, such as tensile testing or dynamic mechanical analysis (DMA). Nanoindentation offers the possibility for quick quasi-nondestructive in situ testing, allowing for monitoring the changes that occur in the surface layer of a plastic micropart. In this study, a methodology for the assessment of the superficial properties: hardness (H) and reduced Young's modulus (Er) of micromolded parts was developed. The microparts, molded from Polyoxymethylene with two different sets of processing conditions were tested throughout the entire length and in the vicinity of the welding line. The observed hardness (H) and reduced Young's modulus (Er) suggest that there is a steady increase in both values along the weld line from the adjoining flow front point at the inner side of the micropart towards the outer edge. In addition, H and Er were found out to vary consistently with the alterations induced by the processing conditions.